Paradoxes of Authoritarian Mundane Surveillance: The Use of Yandex.Eda Data Leak to Investigate the Powerful in Russia - Lysova, Tatiana (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
For years, the Russian authoritarian regime has been seeking to expand its surveillance capacity and collect information on the whole population. The arrival of digital services has made it possible to collect vast amounts of data on their users. Since digital services are frequently designed to assist with various mundane tasks, state-affiliated individuals can also use them, sharing a range of personal data. In Russia, a legal framework has been developed to oblige private digital companies to share collected data with investigative and intelligence agencies. Simultaneously, the collected data, including data on the powerful, may not be adequately protected and, therefore, can be hacked and leaked, thus facilitating sousveillance. This paradox is at the centre of this study, which explores it via the example of the Yandex.Eda, a food delivery service, leak and its use by investigative journalism. This paper, drawing on the concepts of authoritarian surveillance assemblage and mundane surveillance, portrays how authoritarian regimes, through the means of law, engage private digital services in the mundane surveillance of the population. Additionally, the paper draws on the concepts of sousveillance and assemblage of resistance to explore how data leaks from mundane digital services collaborating with authoritarian regimes can stimulate investigation into state actors’ corruption through the work of leaktivism and investigative journalism. The paper shows that although high-profile political actors did not appear in the leak, people closely related to them, along with some lower-ranking special services agents, did. This paper argues that precisely because the app has a mundane nature and sharing personal data with it facilitates its use, these actors left some pieces of their personal information there. In turn, this data sharing has contributed to sousveillance over them.